Adherencia farmacológica y factores asociados en diabéticos tipo 2 en el Instituto Nacional del Diabético - Augusto Alfonso Rosales Meléndez; Clares Shayra Pérez; Mitchel Senaedy Borjas Barahona (Revista Médica Hondureña)
Introduction: A key aspect in the management of type 2 diabetes is medication adherence.In 2023, The overall prevalence of medication adherence was 55%. Objective: To determine the proportion and associated factors of medication adherence in type 2 diabetes patients at the National Institute of Diabetes (INADI) from May to July 2024. Methods: Cross-sectional study with association analysis conducted in adults (≥18 years) with type 2 diabetes, using non-probabilistic quota sampling. A survey was applied, and adherence was assessed using the Morisky-Green scale. The statistical analysis included univariate, bivariate, and multivariate approaches, applying robust Poisson regression. Crude and adjusted prevalence ratios (PR) were estimated, with 95% confidence intervals (CI) and p values ≤0.05. Results: A percentage of medication adherence of 61% was found. The associated factors include high family income (PR: 1.40, 95%CI 1.07-1.83, p=0.01), more than 10 years with the disease (PR: 1.35, 95%CI 1.01-1.82, p=0.04), a positive attitude towards medication (PR: 2.45, 95%CI 1.11-5.39, p =0.02), and consistent family support (PR: 1.41, 95%CI 1.03-1.94, p=0.04). Adverse effects such as hypoglycemia (PR: 0.64, 95%CI 0.49-0.83, p=0.001) and gastrointestinal side effects (PR: 0.68, 95%CI 0.48-0.94, p=0.02) were negatively associated with adherence. Discussion: Medication adherence in type 2 diabetes is influenced by psychosocial, economic, and clinical factors. Addressing these aspects in therapeutic strategies could improve adherence and disease management